Construction of vector and transformation of drought-responsive gene OsNAC1 into J02 (Oryza sativa L. Japonica) rice - Hằng, Phạm Thu; Hiếu, Đàm Quang; Nghĩa, Phan Tuấn; Hội, Phạm Xuân (Vietnam Journal of Biotechnology, 2016)
NAC (including NAM - no apical meristem, ATAF1/2 - Arabidopsis transcription activation factor and CUC2 - cup-shaped cotyledon), which is the largest plant transcription factor family, plays an important role in development and stress responses in plants. Protein of this family is characterized by a highly conserved DNA binding domain, known as NAC domain in the N-terminal region. In contrast, the C-terminal region of NAC proteins, usually containing the transcriptional activation domain, is highly diversified both in length and sequence. More than 100 members of this family have been identified in rice. However, only a few of them have been functionally characterized, especially in rice. Gene encoding transcription factor OsNAC1 has been proved to play an important role in drought stress in plants. The CaMV35S promoter derived from the common plant virus, cauliflower mosaic virus (CaMV), is a component of transgenic constructs in more than 80% of genetically modified (GM) plants. It is the promoter of choice for plant genetic engineering, as it is a strong and constitutive promoter. In this study, an expression vector harboring OsNAC1 in the form of CaMV35S:OsNAC1:Nos was constructed and transferred into J02 (Oryza sativa L. Japonica) rice plants via Agrobacterium tumefaciens. The presence of the transgene was confirmed by PCR using OsNAC1 specific primers. T0 CaMV35S:OsNAC1:Nos transgenic lines were selected from transgenic plants. The obatained results are expected to be further exploited for development of stress tolerant rice varieties in the future.